2007
DOI: 10.1021/ie0702330
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Microorganisms in Carbon Dioxide at Elevated Pressure and Ambient Temperature

Abstract: Microorganisms are inactivated remarkably by carbon dioxide at the elevated pressure. The process can be divided into two phases based on the different rate of inactivation: the rate of inactivation is slower at the initial stage and increased sharply at the later stage. The dissolution of CO 2 into the aqueous solution and then diffusion into cells controls the duration and inactivation rate at the early stage. An increase of pressure and temperature enhances the antimicrobial effect of CO 2 under pressure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…The same phenomena were, also, reported in SC‐CO 2 inactivation (Tanimoto et al. , 2007; Wu et al. , 2007), but it was still not clear why SC‐CO 2 efficiency was enhanced by the addition of ethanol.…”
Section: Resultssupporting
confidence: 52%
“…The same phenomena were, also, reported in SC‐CO 2 inactivation (Tanimoto et al. , 2007; Wu et al. , 2007), but it was still not clear why SC‐CO 2 efficiency was enhanced by the addition of ethanol.…”
Section: Resultssupporting
confidence: 52%
“…Dissolved CO 2 is thought to penetrate the cells, and the generated H 2 CO 3 dissociates into HCO 3 − and H + , leading to acidification of the cytoplasm (Dixon and Kell, 1989;Dillow et al, 1999;Spilimbergo et al, 2002). Acidification of cytoplasm has been shown to induce injury and affect the viability of vegetative microbial cells (Kim et al, 2008;Wu et al, 2007). Although numerous reports have demonstrated that carbonation at moderate temperature (20 − 40℃) can inactivate microorganisms in their vegetative form, this is not sufficient for substantial reductions in viable spore counts (Garcia-Gonzalez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that at room temperature, S. cerevisiae was killed by 2 log reduction by CO 2 treatment under 5 MPa (Debs-Louka et al, 1999). A significant reduction ratio of 8 log was attained at 6 MPa, 40°C (Kumugai et al, 1997), 7.8 MPa at 35°C (Wu et al, 2007), 13 MPa at 50°C (Ferrentino et al, 2010). Ferrentino et al (2010) published a paper in which they described the inactivation effect at different temperatures (35-50°C) and pressures (7.5-13 MPa), and the results show that the effectiveness of inhibition is enhanced under higher temperature and pressure (Table 3).…”
Section: Saccharomyces Cerevisiae Inactivationmentioning
confidence: 97%
“…Schmidt et al (2005) and Cinquemani et al (2007) have found that E. coli was completely inhibited with 5-7 MPa CO 2 in only 20 min. Moreover, an increase of pressure, temperature, or treatment time of CO 2 under pressure enhanced the antimicrobial effect against E. coli (Kamihira et al, 1987;Dillow et al, 1999;Wu et al, 2007;Kobayashi et al, 2007Kobayashi et al, , 2009bGarcia-Gonzalez et al, 2010). Thus the use of pressurized CO 2 has been widely investigated (Wu et al, 2007;Kobayashi et al, 2007Kobayashi et al, , 2009aJung et al, 2009;Garcia-Gonzalez et al, 2010;Klangpetch et al, 2011;Cheng et al, 2011).…”
Section: Gram-negative Bacteria Inactivation (Escherichia Coli)mentioning
confidence: 99%
See 1 more Smart Citation